Implementation of Fulfillment of the Rights to Health, Safety, Comfort, and Convenience for Residents of Begalon II Rusunawa - Fachry, Muhammad Rizqon; Subekti, Rahayu; Raharjo, Purwono Sungkowo (CV. Strata Persada Academia, 2024)
This research aims to examine the fulfillment of the Right to Health, Safety, Comfort, and Convenience by the Surakarta city government, namely the flats Manager for the Begalon II Tipes flats Residents. The background of this research is a complaint from the voice of the Low-Income Community or MBR for the Government to pay more attention to their rights. In addition, the gap between the rights obtained between residents in flats which were built longer is not as good or as appropriate as the rights obtained by residents in flats which were built more recently. The main focus of this research is the fulfillment of health, safety, comfort, and convenience rights that should be fulfilled by the manager fairly. The efforts of the manager in fulfilling these rights are also the focus of this research. This research also describes the rights and obligations of flats residents so that the research is also balanced. This research method is empirical legal research. Primary data is obtained through interviews with the Head of UPT Rusunawa of the Surakarta City Housing and Settlement Office and residents of Begalon Tipes II flats. While secondary data is sourced from legal literature, laws and regulations, and from various related sources of information. Data analysis is done qualitatively by referring to the rights of occupants of houses or buildings from various laws and regulations. The results of this research are expected to contribute to the understanding of the implementation of regulations on flats and the protection of the rights of residents, especially the rights to health, safety, comfort, and convenience.